Reduction of Blowholesin Aluminium High Pressure Die Casting Machine - P, Nagasankar; V, Sathiyamoorthy.; P, Gurusamy.; P, VinothKanna; D, Manibharathi; P, Srikanth (International Journal of Engineering and Technology, 2018)
The main objective of this research is to reduce the blowholes by analyzing the factors which are affected during the casting process. The process parameters are optimized and change is made in the design part to reduce the blowhole and to increase the efficiency of the high pressure die casting machines. Product manufactured from every manufacturing process shows some defects. For supplying quality product to the customer these defects must be reduced. In this work, an attempt is made to reduce the rejection due to the blowhole defect is found out through why-why analysis technique. Process capability of current high pressure die casting manufacturing process is checked. Manufacturing process found capable to manufacture the components. Current problem of blowhole defect is solved making an improvement in design of die which we insert. In gate directions are changed so as to obtain modified improved flow pattern. Using magma flow simulationsoftware existing and modified design has then been compared. It is found that, modified design shows superior results and using this, the defect of blowholes is minimized up to satisfactory level.Â Â Â